2020
DOI: 10.21203/rs.3.rs-20811/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COL4A1 promotes the growth and metastasis of hepatocellular carcinoma cells by activating FAK-Src signaling

Abstract: Background: Collagens are the most abundant proteins in extra cellular matrix and important components of tumor microenvironment. Recent studies have showed that aberrant expression of collagens can influence tumor cell behaviors. However, their roles in hepatocellular carcinoma (HCC) are poorly understood. Methods: In this study, we screened all 44 collagen members in HCC using whole transcriptome sequencing data from the public datasets, and collagen type IV alpha1 chain (COL4A1) was identified as its most s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 43 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…The results indicated that the expression levels of COL4A1 in glioma tissues were significantly higher than those in normal brain tissues. This is supported by previous reports that COL4A1 expression is increased in malignant tumors (16,24,25,28). For instance, COL4A1 expression is also increased in numerous types of malignant tumor tissue (such as esophageal squamous cell carcinoma, renal cell carcinoma, urothelial carcinoma of the bladder and breast cancer) and has an important impact on the occurrence and development of cancer (16,20,24,28).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results indicated that the expression levels of COL4A1 in glioma tissues were significantly higher than those in normal brain tissues. This is supported by previous reports that COL4A1 expression is increased in malignant tumors (16,24,25,28). For instance, COL4A1 expression is also increased in numerous types of malignant tumor tissue (such as esophageal squamous cell carcinoma, renal cell carcinoma, urothelial carcinoma of the bladder and breast cancer) and has an important impact on the occurrence and development of cancer (16,20,24,28).…”
Section: Discussionsupporting
confidence: 86%
“…Various studies have indicated that COL4A1 is involved in the pathological process of a variety of cancer types and has a key role in their occurrence, development and metastasis (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…41,42 On top of this, the high expression of COL4A1 promotes proliferation, invasion, and migration in hepatocellular carcinoma (HCC) via activation of FAK-Src signaling. 43 Collagen alpha-2(I) chain is a protein encoded by the COL1A2 gene, which is the bulk significantly rich form of collagen in humans. At the same time, numerous studies have revealed that COL1A2 is closely related to cancers.…”
Section: Discussionmentioning
confidence: 99%
“…COL4A1 may play a critical function in the proliferation and colony formation of breast cancer cells. In particular, recent experimental results indicated that silencing COL4A1 expression in hepatocellular carcinoma HepG2 cells significantly inhibited the capacity for proliferation, migration and invasion [37]. Inhibition of COL4A2 gene expression in hepatocellular carcinoma cells attenuated the proliferation and migration ability of hepatocellular carcinoma cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recent experimental results indicated that silencing COL4A1 expression in hepatocellular carcinoma HepG2 cells significantly inhibited the capacity for proliferation, migration and invasion [37]. Inhibition of COL4A2 gene expression in hepatocellular carcinoma cells attenuated the proliferation and migration ability of hepatocellular carcinoma cells [37]. COL4A2 can be regarded as a core gene in the pathogenesis of breast cancer and has a prognostic value in breast cancer [38].…”
Section: Discussionmentioning
confidence: 99%